Empirical Differences between UAE and Finland of Strategic Foresight Implementation - Ahmed Lari, Fatma; Abdulla Lari, Darwish Ahmed Darwish; Abdulla Lari, Mohamed Ahmed Darwish (International Journal of Sustainable Construction Engineering and Technology, 2020)
Strategic foresight is a structured and systematic way of using ideas to anticipate and better prepare for change in the future. Therefore, the main aim of the study is to ascertain whether there is difference between UAE and Finland strategic foresights implementation. This study employed quantitative methodology where questionnaire was used as a means for data collection. The data was analysed using SPSS software to ascertain the difference between the means across the strategic foresight dimensions between the two countries. The result findings revealed that that there is statistically significant difference between UAE and Finland’s in the areas of Information use and method sophistication of the two countries’ strategic foresights. Specifically, UAE and Finland differs on information use in their strategic foresights. Similarly, the two countries differ on method sophistication in their strategic foresight. However, there is no significant difference between UAE and Finland on people and network, organisation and culture in their strategic foresights. This specify that the respondents from Finland and UAE had agreed almost similar factors in strategic foresight for the public policy making. Hence if taking Finland as a benchmark, the results indicate that UAE is also having the same interest in strategic foresight implementation.